Protein kinase C-α (PKCα) modulates cell apoptosis by stimulating nuclear translocation of NF-kappa-B p65 in urothelial cell carcinoma of the bladder - Zheng, Jin (BMC Cancer, 2017)
BACKGROUND: The protein kinase C (PKC) family comprises central regulators of multiple signal transduction processes and is involved in the progression of many cancers. Nuclear factor Kappa-B (NF-κB) is constitutively expressed in cancer tissues and stimulates the transcription of various tumor-related genes. The present study aims to investigate the clinical significance of PKCα and NF-κB p65 in bladder cancer tissues and the mechanism underlying PKCα induction of bladder cancer cell apoptotic resistance through stimulation of p65 nuclear translocation. METHODS: Expression of PKCα and NF-κB subunit p65 was detected in seven bladder cancer cell lines by western blot and in 30 bladder cancer tissue specimens by immunostaining. Immunofluorescence was performed to evaluate p65 nuclear translocation induced by Phorbol 12-myristate 13-acetate (PMA). PKCα/β selective inhibitor Gö6976, PKC pan-inhibitor sotrastaurin, and the PKC siRNA were employed to conduct PKC inhibition/knockdown in bladder cancer cells. Luciferase reporter assays were performed to measure the activity of NF-κB. Flow cytometry and TUNEL analysis were used to assess cell apoptosis. RESULTS: Expression of PKCα and NF-κB was found to positively correlate with tumor progression in 30 tumor tissue specimens. Furthermore, a Pearson’s correlation coefficient analysis revealed a positive correlation between PKCα and NF-κB expression. Among the PKC inhibitors, the PKCα/β selective inhibitor Gö6976 yielded the most significant block of PKCα and NF-κB activation by PMA. Knockdown of NF-κB p65 remarkably induced cell apoptosis, but PMA restored p65 expression and significantly suppressed cell apoptosis that was otherwise induced by the p65 knockdown alone. CONCLUSION: Our study showed that PKCα modulated cell resistance to apoptosis by stimulating NF-κB activation and thus promoted the tumorigenesis of bladder cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12885-017-3401-7) contains supplementary material, which is available to authorized users.